Funcionalização química de nanofitas de fosforeno de bordas reconstruídas – propriedades estruturais e eletrônicas - Castro, Giselle dos Santos (2019)
Phosphorene is a direct gap semiconductor, of approximately 2.0 eV, with high electronic mobility. Its structural and electronic properties can be modified when it is “cut” and adapted into derived nanostructures, as nanoribbons. The physical properties of phosphorene nanoribbons are dependent on their crystalline form and edge configuration. In this work, we use the first principles calculation based on density functional theory to study the effects of phosphorene nanoribbons surface functionalization of reconstructed edges (self passivated) on the structural and electronic properties of the system upon adsorption. Different chemical elements, such as Li, O, F and Cl, in concentrations of 1/32, 1/16 and 1/8 were applied.